Uwięzieni we wnętrzu - "Motyl i skafander" Juliana Schnabela i "Tajemniczy płomień królowej Loany" Umberto Eco - Front, Sonia (Er(r)go. Teoria - Literatura - Kultura, 2012)
Sonia Front Trapped in the Interiors: Julian Schnabel’s The Diving-Bell and the Butterfly and Umberto Eco’s The Mysterious Flame of Queen Loana Both Jean-Dominique Baube, the protagonist of The Diving-Bell and the Butterfly (2007), and Yambo, the protagonist of Umberto Eco’s The Mysterious Flame of Queen Loana (2004), have become imprisoned in their bodies as a result of accidents. What a viewer and the reader are presented with is the view from the interiors of the subjects suspended from their sensory-motor continuity. Both attempting to put their past in order, they experience a kind of immeasurable subjective time; a perpetual present. The paper explores the significance of the dislocation from the linear continuity of spatialized time to the characters and its influence on their selves by means of Gilles Deleuze’s theory of time-image.